Constitutional Reconstruction of Customary Land Rights Protection in the Development of Indonesia’s New Capital - Abrori, Achmad Fagil; Anwar, Sophia Rahma Sari; Rohmah, Elva Imeldatur (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Abstract: The relocation of the National Capital City (IKN) from Jakarta to East Kalimantan, as outlined in Law No. 3/2022, poses a serious challenge to the recognition and protection of the customary rights of indigenous peoples. Although Article 18B paragraph (2) of the 1945 Constitution and its derivative regulations (UUPA, UU IKN, PP 65/2022, Permen ATR 18/2019) provide a juridical basis, implementation in the field is still hampered by the absence of a Regional Regulation on customary recognition, overlapping land claims, and low participation of indigenous peoples. This study employs an analytical normative-descriptive legal approach, utilizing secondary data sources to map the legal framework, document forms of tenure conflicts, and assess the gap between juridical expectations and the reality of implementation. The results of the analysis revealed that the absence of a formal mechanism for recognition and SOPs for customary land registration led to the vulnerability of customary rights to land conversion. Constitutional Court Decision No. 35/PUUX/2012, which recognizes customary forests, has not been followed by concrete legislative steps. As a solution, it is suggested to revise and harmonize UUPA regulations, ratify customary recognition regulations, participatory mapping, prepare SOPs for customary land registration, and FPIC-based dispute resolution mechanisms to realize inclusive and equitable IKN development. Keywords: customary rights, indigenous peoples, land conflicts, the capital city of the archipelago, constitutional protection. Abstract: Pemindahan Ibu Kota Negara (IKN) dari Jakarta ke Kalimantan Timur melalui UU No. 3/2022 menimbulkan tantangan serius bagi pengakuan dan perlindungan hak ulayat masyarakat adat. Meskipun Pasal 18B ayat (2) UUD 1945 dan regulasi turunannya (UUPA, UU IKN, PP 65/2022, Permen ATR 18/2019) memberikan landasan yuridis, pelaksanaan di lapangan masih terhambat oleh ketiadaan Perda pengakuan adat, tumpang‑tindih klaim lahan, dan rendahnya partisipasi masyarakat adat. Studi ini menggunakan pendekatan hukum normatif-deskriptif analitis dengan sumber data sekunder untuk memetakan kerangka hukum, merekam bentuk-bentuk konflik tenurial, serta menilai kesenjangan antara harapan yuridis dan realitas implementasi. Hasil analisis mengungkap bahwa kurangnya mekanisme formal pengakuan dan SOP pendaftaran tanah ulayat menyebabkan rentannya hak ulayat terhadap alih fungsi lahan. Putusan MK No. 35/PUU‑X/2012 yang mengakui hutan adat belum diikuti oleh langkah legislatif konkret. Sebagai solusi, disarankan perevisian dan harmonisasi regulasi UUPA, pengesahan Perda pengakuan adat, pemetaan partisipatif, penyusunan SOP pendaftaran tanah ulayat, dan mekanisme penyelesaian sengketa berbasis FPIC untuk mewujudkan pembangunan IKN yang inklusif dan berkeadilan. Keywords: hak ulayat, masyarakat adat, konflik lahan, Ibu Kota Nusantara, perlindungan konstitusional.